Taxonomic revision of the Phanaeus endymion species group (Coleoptera: Scarabaeidae), with the descriptions of five new species - Moctezuma, Victor; Halffter, Gonzalo (European Journal of Taxonomy, 2021)
The Phanaeus endymion species group is defined as a lineage of dung beetles distributed from Mexico to Ecuador. The current arrangement of the P. endymion species group includes 18 species (five newly described and three revalidated herein): P. arletteae Arnaud, 2018; P. bravoensis Moctezuma, Sánchez-Huerta & Halffter, 2017; P. chiapanecus sp. nov.; P. edmondsi Moctezuma, Deloya & Halffter, 2019; P. endymion Harold, 1863; P. funereus Balthasar, 1939 stat. rev.; P. halffterorum Edmonds, 1979; P. huichol Moctezuma, Sánchez-Huerta & Halffter, 2017; P. jackenioi sp. nov.; P. malyi Arnaud, 2002; P. olsoufieffi Balthasar, 1939 stat. rev.; P. pacificus sp. nov.; P. panamensis sp. nov.; P. porioni Arnaud, 2001 stat. rev.; P. pyrois Bates, 1887; P. rzedowskii sp. nov.; P. zapotecus Edmonds, 2006; and P. zoque Moctezuma & Halffter, 2017. Phanaeus dionysius Kohlmann, Arriaga-Jiménez & Rös, 2018 syn. nov. is considered as a new junior subjective synonymy of P. zapotecus Edmonds, 2006. Phanaeus blanchardi Olsoufieff, 1924 and P. bothrus Blackwelder, 1944 are junior objective synonyms of P. olsoufieffi Balthasar, 1939 stat. rev.